2011
DOI: 10.3109/00207454.2010.546537
|View full text |Cite
|
Sign up to set email alerts
|

Structured Exercise Does Not Stabilize Cognitive Function in Individuals With Mild Cognitive Impairment Residing in a Structured Living Facility

Abstract: Exercise has been shown to have positive effects on the brain and cognition in healthy older adults, though no study has directly examined possible cognitive benefits of formal exercise programs in persons with mild cognitive impairment (MCI) living in structured facilities. Thirty one participants completed neuropsychological testing and measures of cardiovascular fitness at baseline and after 6 months of a structured exercise program that included aerobic and resistance training. While exercise improved card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
10
1
2
Order By: Relevance
“…Two studies that reported a failure of improvement in neurocognitive performance in MCI after an exercise intervention suffer from somewhat questionable efficacy of the intervention [61, 62]. In contrast, another study reported improved verbal fluency, Stroop Color-Word Interference and Symbol-digit Modalities Test performance after a 6-month exercise intervention, which evidenced a comparable increase in fitness as achieved in the current study (11.5% vs. 10.6% in the current study) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies that reported a failure of improvement in neurocognitive performance in MCI after an exercise intervention suffer from somewhat questionable efficacy of the intervention [61, 62]. In contrast, another study reported improved verbal fluency, Stroop Color-Word Interference and Symbol-digit Modalities Test performance after a 6-month exercise intervention, which evidenced a comparable increase in fitness as achieved in the current study (11.5% vs. 10.6% in the current study) [29].…”
Section: Discussionmentioning
confidence: 99%
“…In a 6‐month, randomized, controlled trial [179], subjects who exercised at a moderate intensity level demonstrated significant improvements on the Alzheimer Disease Assessment Scale (Alzheimer’s diseaseAS‐Cog). Despite these positive findings, however, another recent study that employed a multi‐modal exercise programme for older adults with mild cognitive impairment who lived in a structured living environment failed to show improvements in cognitive function despite an enhanced cardiovascular profile [180]. The reason behind this discrepancy is not clear, but may suggest that, as cognitive impairment progresses and a greater level of structure is required, individuals may benefit to a lesser degree from exercise intervention.…”
Section: Lifestyle Modification: Strategies For Preventionmentioning
confidence: 99%
“…Among those already cognitively impaired, most prospective exercise trials documented significant cognitive benefits [146][147][148][149][150][151][152][153][154][155] ; however, a few reported only modest outcomes, [156][157][158] with 1 negative study. 159 The most recent metaanalysis assessing RCTs of aerobic exercise in demented patients reported significant positive effects on cognition. 160 Although 2 earlier meta-analyses of long-term exercise in demented patients were negative, they included numerous trials using nonaerobic interventions.…”
Section: Establishedmentioning
confidence: 99%